Open lung biopsy in neonatal and paediatric patients referred for extracorporeal membrane oxygenation (ECMO). Issue 4 (26th March 2004) - Inwald, D; Brown, K; Gensini, F; Malone, M; Goldman, A
Abstract : Background: This study was undertaken to determine the usefulness, safety, and most appropriate timing of open lung biopsy in infants and children considered for and on extracorporeal membrane oxygenation (ECMO) for respiratory failure. Methods: A retrospective review of children referred for consideration of and placed on ECMO in our institution in the period 1996–2002. Results: 506 patients were referred, 15 (3%) of whom underwent antemortem open lung biopsy (eight neonatal, four paediatric, and three cardiac patients). In the neonatal group open lung biopsy contributed to clinical decision making in all patients. Four neonates had a fatal lung dysplasia (three alveolar capillary dysplasia and one surfactant protein B deficiency) and treatment was withdrawn. Of the other four neonates, two had pulmonary hypoplasia, one had pulmonary lymphangiectasia, and one had meconium aspiration with mild barotrauma. Treatment was continued in these four patients and two survived. In the paediatric group the biopsies were of clinical relevance in two infants with pertussis who had lung infarction on biopsy in whom treatment was withdrawn. In the other two paediatric patients the biopsies were equivocal, treatment was continued, but both patients died. In the cardiac group, who presented perioperatively with pulmonary hypertension, the biopsies excluded a fatal lung dysplasia and severe pulmonary vascular disease but all three infants died. One patient had non-fatal bleeding complications. Conclusion: Open lung biopsy is clinically most useful when performed to diagnose fatal lung dysplasias in neonates and to confirm the presence of viable lung tissue in patients with acute lung injury due to pertussis infection.